2008
DOI: 10.1021/jp8038175
|View full text |Cite
|
Sign up to set email alerts
|

Fourier Transform Infrared Studies in Hypergolic Ignition of Ionic Liquids

Abstract: Public reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing this collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing this burden to Department of Defense, Washington Headquarters Services, Directorate for Info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
194
0
12

Year Published

2009
2009
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 126 publications
(223 citation statements)
references
References 69 publications
17
194
0
12
Order By: Relevance
“…[4] Since 2008, a number of ILs have been reported to be hypergolic when treated with common oxidizers, such as HNO 3 . [5][6][7] Of particular practical interest are hypergolic ILs comprising fuel-rich dicyanamide (DCA) anions. [5] The DCA ILs have some of the lowest viscosities among known ILs, [8] which is a very important figure of merit for the efficient fuel supply in bipropellant engines.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[4] Since 2008, a number of ILs have been reported to be hypergolic when treated with common oxidizers, such as HNO 3 . [5][6][7] Of particular practical interest are hypergolic ILs comprising fuel-rich dicyanamide (DCA) anions. [5] The DCA ILs have some of the lowest viscosities among known ILs, [8] which is a very important figure of merit for the efficient fuel supply in bipropellant engines.…”
mentioning
confidence: 99%
“…The concurrent formation of precipitate siphons materials from the hypergolic reaction pathway, [6] thus limiting the energy capacity of a fuel. Our rough measurements indicate that about 25% of DCA IL is converted into precipitate during the ignition.…”
mentioning
confidence: 99%
“…After a general introduction on the interesting results recently observed in this field by Chambreau and Vaghjiani et al (2008) at the Air Force Research Laboratory (AFRL), Edwards AFB, this report will discuss the thermochemistry of imidazoles, triazoles, tetrazoles, and nitro compounds, which are energetic compounds for which relatively little thermodynamic data is available. Then, the reactivity of the gas phase above the reacting ILs-WFNA liquid mixtures will be examined by performing calculations at thermodynamic equilibrium as described in interim report # 2.…”
Section: References 42mentioning
confidence: 99%
“…Actually, Chambreau and Vaghjiani et al (2008) showed that ILs and WFNA react exothermically in the liquid phase to form products in the liquid phase that then elute into the gas phase. This is further discussed in section 5.…”
Section: Aprotic Ionic Liquidsmentioning
confidence: 99%
See 1 more Smart Citation